ANALISIS KEPUTUSAN PETANI DALAM USAHATANI PADI ORGANIK DAN PADI ANORGANIK DI LAHAN IRIGASI KECAMATAN BELITANG III KABUPATEN OGAN KOMERING ULU TIMUR - Trinawati Trinawati; Maryadi Maryadi; Dessy Adriani (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2018)
The purpose of this study was: 1) to describe the differences in cultivation techniques of organic andanorganic rice farming in Irrigated land, Belitang III District, Ogan Komering Ulu Timur, 2) to analyze theproductivity and farm revenue of organic and anorganic rice farming in Irrigated land, Belitang III District, OganKomering Ulu Timur, 3) to analyze factors that influence farmers decision in organic and anorganic rice farming in irrigated land, Belitang III District, Ogan Komering Ulu Timur. The data collection was conducted during December 2016. The research method was a survey, which the rice farmers of organic and anorganic as the study sample. Samples of farmers were 30 farmers of organic rice and 30 of anorganic rice farmers where they are members of a farmers' group called "Gapoktan Maju Bersama". The data used are primary and secondary data. The results of the research showed that the organic rice cultivation techniques for maintence activities used plants that exist around the fields to be used as fertilizer and pesticides were processed using organic additivies. Pest and disease control was done manually by pulling with hand or tools such as sickles, hoes and machetes. While the technique of anorganic cultivation used chemicals in maintenance, fertilizing and pest and disease control. On production there is a real difference between organic and anorganic rice farming. Productivity per year, organic rice farming is higher thananorganic rice farming. Then, revenue in organic rice farming also higher than rice farming anorganic. Factors that is fluence of farmers decisions in organic and anorganic rice farming is a fixed cost, variable cost, land area, numberof dependents, level of education and age levels, while the negative effect is the amount of production.